The Limits of "Communication Mode" as a Construct. (20th May 2020) - Hall, Matthew L; Dills, Sheila
Abstract: Questions about communication mode (a.k.a. "communication options" or "communication opportunities") remain among the most controversial issues in the many fields that are concerned with the development and well-being of children (and adults) who are d/Deaf or hard of hearing. In this manuscript, we argue that a large part of the reason that this debate persists is due to limitations of the construct itself. We focus on what we term "the crucial question": namely, what kind of experience with linguistic input during infancy and toddlerhood is most likely to result in mastery of at least one language (spoken or signed) by school entry. We argue that the construct of communication mode—as currently construed—actively prevents the discovery of compelling answers to that question. To substantiate our argument, we present a review of a relevant subset of the recent empirical literature and document the prevalence of our concerns. We conclude by articulating the desiderata of an alternative construct that, if appropriately measured, would have the potential to yield answers to what we identify as "the crucial question."